Peri- and intraarticular analgesia (PIA) superior to other procedures in TKA – review of literature and results of own RCT. Issue 3 (23rd March 2016) - Beckmann, J.; Stathellis, A.; Fitz, W.; Köck, F.; Bauer, G.; Gebauer, M.; Schnurr, C.
Background: TKA is a worldwide established surgery with periarticular infiltrations being scientifically funded is the superiority of in the perioperative setup of TKA nowadays. However, nerve blocks are still widely used as perioperative standard meaning possible analgesia beyond surger, but simultaneously with sensomotoric deficiency and resulting risk of fall as well as increased pain after removal of nerval catheters. Also a standard procedure is intubation which means immediate pain after awakening of patients with resulting need for sufficient oral, intravenous, intramuscular or subcutaneous analgesia. We present an actual review of the literature and an own RCT comparing infiltrations with nerve blocks, which to our best knowledge presents the first RCT combined with an additional continous part. Methods: Literature review (PubMed) Own RCT: 50 TKA were randomized and prospectively included. 25 patients received nerve blocks with a single ischiadicus block and a femoralis block with additional perineural catheter. 25 patients received periarticular infiltrations together with an intraarticular catheter (PIA). All catheters stayed for 4 days. Both groups received a laryngeal masc. Postoperative mobilisation, surgeon and type of prosthesis were the same in all patients. The following was evaluated pre- and postoperatively (first, third and sixth hour, first until sixth day): VAS, additional analgetics/ opioids, KSS score, knee function and ability to raise the straightened leg. Complications as infection, falls, DVT etc. were recorded. Results: Periarticular infiltrations are superior to other options in the perioperative setup of TKA which is clearly shown by literature (several studies including reviews) as well as the results of our own RCT: Pain occured in both groups, however, VAS, additional analgetics/ opioids and KSS score as well as the ability to raise the straightened leg were significantly better following PIA (p<0, 01), with comparable knee function in both groups. There were two falls and one superficial infection of catheter site following nerve blocks, however, without sequelae. Conclusion: All analgesic/ anaesthetic options can be done perioperatively in TKA with success with, however, clear superiority of PIA. Compared to nerve blocks PIA reduces the risk for falls, prevents a pain-„rebound" with removal of perineural catheters and is beneficial for patients throughout the whole hospitalisation.